A flexible and extensible object middleware CORBA and beyond. - Hauck, Franz J. (Software engineering notes.)
This paper presents a CORBA-compliant middleware architecture that is more flexible and extensible compared to standard CORBA. The portable design of this architecture is easily integrated in any standard CORBA middleware; for this purpose, mainly the handling of object references (IORs) has to be changed. To encapsulate those changes, we introduce the concept of a generic reference manager with portable profile managers. Profile managers are pluggable and in extreme can be downloaded on demand. To illustrate the use of this approach, we present a profile manager implementation for fragmented objects and another one for bridging CORBA to the Jini world. The first profile manager supports truly distributed objects, which allow seamless integration of partitioning, scalability, fault tolerance, end-to-end quality of service, and many more implementation aspects into a distributed object without losing distribution and location transparency. The second profile manager illustrates how our architecture enables fully transparent access from CORBA applications to services on non-CORBA platforms.